Unilateral application of cathodal tDCS reduces transcallosal inhibition and improves visual acuity in amblyopic patients. Issue 1 (January 2019) - Bocci, T.; Nasini, F.; Caleo, M.; Restani, L.; Ardolino, G.; Priori, A.; Maffei, L.; Nardi, M.; Sartucci, F.
Abstract : Amblyopia is a neurodevelopmental disorder characterized by visual acuity and contrast sensitivity loss, refractory to pharmacological and optical treatments in adulthood. We studied the response of the visual cortex to transcranial Direct Current Stimulation (tDCS) applied over the primary visual area (V1) contralateral to the "lazy eye". Visual acuity (logMAR) was assessed before (T0), immediately after (T1) and 60′ following the application of cathodal tDCS (2.0 mA, 20′). At each time point, Visual Evoked Potentials (VEPs) triggered by grating stimuli of different contrasts (K90%, K20%) were recorded in both hemispheres and compared to those obtained in healthy volunteers. Cathodal tDCS improved visual acuity (Holm–Sidak, p < 0.0001), whereas sham polarization had no significant effect. tDCS produced an inhibitory effect on VEPs amplitudes in the targeted side and a concurrent facilitation of responses in the hemisphere ipsilateral to the amblyopic eye; the facilitation persisted at T2 for high contrasts (K90%; p < 0.001), while the stimulated hemisphere recovered more quickly from inhibition (p < 0.001). tDCS is a promising treatment for amblyopia in adults. The recovery of excitability and the persistent transcallosal disinhibition following tDCS support the role of interhemispheric pathways in the pathophysiology of amblyopia.